Rapid antibiotic susceptibility testing and species identification for mixed samples - Karempudi, Praneeth; Vinodh, Kandavalli; Larsson, Jimmy; Elf, Johan (Uppsala University, 2022)
General description

This item contains all the data, code and analysis objects used in the paper:

"Rapid antibiotic susceptibility testing and species identification for mixed samples

Vinodh Kandavalli*, Praneeth Karempudi*, Jimmy Larsson & Johan Elf.

Dept. Cell and Molecular Biology, Uppsala University, Sweden"

*Equal contribution

Experimental data description

All the experiments done in this paper are timelapse microscopy experiments. Each experiment contains two directories, one containing phase contrast images arranged by positions images on microfluidic device described in the paper. The other contains fluorescence images, also arranged by positions. Phase contrast images are used for phenotyping bacteria growing in fluidic channels and fluorescence images are used for determining genotype of the cells. Unless stated specifically the lower number of positions (100 series) are cells not treated with antibiotic and the upper series of positions (200 series) are for positions treated with antibiotics. Each series corresponds to one side of the fluidic device.

Experiments can be broadly divided into 4 categories.

1. Single fluorescence channel per Species

In this kind of experiments, each species is colored/stained by one fluorescence probe that is specific to it's ribosomal RNA. There are 4 experiments of this kind in this dataset, all of which are used in making Fig3 of the main manuscript. All these experiments had 4 speices E.coli, E.faecalis, K.pneumoniae, P.aeruginosa. They are in the following zips.

a) data_EXP-21-BV6157.zip (Ciprofloxacin 1ug/ml)

b) data_EXP-21-BV6160.zip (Gentamycin 2ug/ml)

c) data_EXP-21-BV6171.zip (Nitrofurantion 32ug/ml)

d) data_EXP-21-BV6174.zip (Vancomycin 4ug/ml)

2. Single or dual fluorescence channel per Species

In this kind of experiments, each species can be colore/stained by either one or two probes at the same time. There are 8 experiments of this kind in this dataset, in which we treat the cells on one side of the chip with antibiotic. There are 4 other experiments of this kind, which are control experiments to show the specificity of the FISH probes. Each of the following experiments has 2 species loaded on to the fluidic device. For these series of experiments we use some of the following 7 species E.coli, E.faecalis, K.pneumoniae, S.aureus, P.aureginosa, P.mirabilis, A.baumannii.

a) data_EXP-22-BV6194.zip (K.pneumoniae, S.aureus, Ciprofloxacin 1ug/ml)

b) data_EXP-22-BV6196.zip (P.aureginosa, A.baumannii, Gentamycin 2ug/ml)

c) data_EXP-22-BV6197.zip (E.coli, P.mirabilis, Nitrofurantoin 32ug/ml)

d) data_EXP-22-BZ0300.zip (E.coli, E.faecalis, Vancomycin 4ug/ml)

e) data_EXP-22-BZ0312.zip (K.pneumoniae, S.aureus, Ciprofloxacin 1ug/ml)

f) data_EXP-22-BZ0306.zip (P.aureginosa, A.baumannii, Gentamycin 2ug/ml)

g) data_EXP-22-BZ0313.zip (E.coli, P.mirabilis, Nitrofurantoin 32ug/ml)

h) data_EXP-22-BZ0307.zip (E.coli, E.faecalis, Vancomycin 4ug/ml)

i) data_EXP-22-BV6188.zip (E.coli, K.pneumoinae, Control expt)

j) data_EXP-22-BV6189.zip (P.aureginosa, E.faecalis, Control expt)

k) data_EXP-22-BV6190.zip (P.mirabilis, A.baumannii, Control expt)

l) data_EXP-22-BV6191.zip (S.aureus, Control expt)

m) data_EXP-22-BZ0308.zip (E.coli, E.faecalis, Loading ratio control expt)

n) data_EXP-22-BZ0314.zip (E.coli, E.faecalis, Loading ratio control expt)

o) data_EXP-22-BV6195.zip (All seven species)

3. Analysis experiment and model development.

The data and code used developing segmentation, tracking and FISH classification models are in the following experiment. This experiment as mulitple directories containing data (data directory), dbscan-python (cloned code for paralled-dbscan implementation, compile for your own architectures), narsil2 (our pipeline code for all the analysis done in the paper, you will have to install this package in an environment using anaconda from .yml files provided), notebooks (notebooks for running various tasks and some sample notebooks), saved_models (directory containing all the models applied in the paper). These are all bundled in the following experiment.

a) data_EXP-22-BP0394.zip

4. Extra experiments from which supplementary videos were made

a) data_EXP-21-BV6169.zip S3 video

b) data_EXP-21-BV6175.zip S1 video

Analyis Objects

All processed data for each of the experiments described are bundle together into on zip. Inside this file there is a zip file for each of the experiments describe in 1, 2 sections above. Each of this zip file contains all the analysis object corresponding to a single experiment. All the AST figures in the paper are done using these analysis objects. They are in the file named

a) analysis_zips.zip

Code

Code used for paper is seperated in this smaller directory without the raw data used for model development. This code zip has all the code, saved_models, notebooks used to replicate all the analysis done in the paper and all the raw figures generated by the notebooks. narsil2 directory has the python package that needs to be installed in a new environment. saved_models has all the models used in the paper. notebooks directory has jupyter notebooks for analysis of all the experiments in expt_notebooks directory. paper_figures directory has all the code organized according to figure numbers and has all the instructions written to replicate the figures/table in the paper.

README.txt file in code_paper.zip also provides description on how to replicate figures shown in the paper.
Keywords: Microbiology not elsewhere classified; Medical and Health Sciences; Medicin och hälsovetenskap; Microbiology; Mikrobiologi